Etiological study of microcytic hypochromic anemia - S Kafle; M Lakhey (Association of Clinical Pathologists of Nepal, 2016)
Background: Microcytic hypochromic anemia is a distinct morphologic subtype of anemia with well- de ned etiology and treatment. The objective of this study was to determine the etiology and frequency of microcytic hypochromic anemia. Materials and Methods: This cross-sectional observational study was conducted at Kathmandu Medical College Teaching Hospital. One hundred cases of microcytic hypochromic anemia were included. Relevant clinical history, hemogram, reticulocyte count, iron pro les were documented in a proforma. Bone marrow aspiration and hemoglobin electrophoresis was conducted when required. Data was analysed by Microsoft SPSS 16 windows. Result: Iron de ciency was the commonest etiology (49%). Dysfunctional uterine bleeding (20.8%) was the commonest cause of iron de ciency, malignancy (24.3%) was the commonest cause of anemia of chronic disease. Mean value of Mean Corpuscular Volume was lowest in hemolytic anemia (71.0 ). Mean Red cell Distribution Width was normal (14.0%) in hemolytic anemia but was raised in other types. Mean serum iron was reduced in iron de ciency anemia (32.2μg/dl) and chronic disease (34.8μg/dl), normal in hemolytic anemia (83μg/dl) and raised in sideroblastic anemia (295μg/dl). Mean serum ferritin was reduced in iron de ciency anemia (7.6ng/ml), raised in chronic disease (158.6ng/ml) and normal in hemolytic anemia (99.2ng/ml). Serum ferritin was normal in sideroblastic anemia (93ng/ml). Mean Total Iron Binding Capacity was raised in iron de ciency anemia (458μg/dl) and normal in other microcytic hypochromic anemias. Conclusion: Diagnosis of microcytic hypochromic anemia requires a standardized approach which includes clinical details, hemogram, peripheral blood smear, reticulocyte count, iron pro le, hemoglobin electrophoresis and bone marrow examination.